2022
DOI: 10.1177/21582440221079923
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Discrepancies Between Online Pornography Created Ideals and Actual Sexual Relationships in Heterosexual Men’s Sexual Satisfaction and Well-Being

Abstract: Contemporary sexually explicit Internet materials (SEIM) are commonly unrealistic. Following from self-discrepancy theory, we proposed that discrepancies between ideal and actual sexual experiences depicted in SEIM (ideal-actual sexual discrepancy; IASD) may be important in understanding the association between SEIM consumption, sexual satisfaction, and general well-being for heterosexual men. Participants from a general online community ( n = 195) were assessed via an online survey. Path analysis showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 115 publications
(210 reference statements)
0
0
0
Order By: Relevance
“…As a result, many scholars believe that depression is a major consequence of cybersex addiction in children because sufferers experience feelings of shame, guilt, and remorse (Glowiak, 2022). In relation to this study, according to Kuan et al (2022), low quality education value is also considered as psychological damage. This is because when children are addicted to cybersex, they are busy fulfilling their sexual fantasies, exploring sexual curiosity, learning about sex and others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, many scholars believe that depression is a major consequence of cybersex addiction in children because sufferers experience feelings of shame, guilt, and remorse (Glowiak, 2022). In relation to this study, according to Kuan et al (2022), low quality education value is also considered as psychological damage. This is because when children are addicted to cybersex, they are busy fulfilling their sexual fantasies, exploring sexual curiosity, learning about sex and others.…”
Section: Resultsmentioning
confidence: 99%
“…Among the six categories of physical damage, this study has identified that relationship problems are the major implications of cybersex addiction involving children. Based on the study undertaken by Kuan et al (2022), it was stated that relationship problems such as break-up and divorce are correlated with higher cybersex consumption due to disruption of sexual intimacy. This is because when the partner is addicted to cybersex, they tend to differentiate themselves physically with the online women or men through pornographic materials.…”
Section: Tablementioning
confidence: 99%